THE INFLUENCE OF PERSONAL FACTORS, ORGANIZATIONAL FACTORS, NON-ORGANIZATIONAL FACTORS AND SELF-EFFICACY ON THE ORGANIZATIONAL COMMITMENT OF PT. KOREAN BUSSINESS NETRWORK INDONESIA - Fatmah Bagis; Humrotul Hasanah; Hengky Widhiandono; Totok Haryanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aims to determine and analyze the influence of personal factors, organizational factors, non-organizational factors and self-efficacy on the organizational commitment of PT. Korean Indonesia Business Network. Sampling using incidental sampling method through a questionnaire. The sample used is 143 employees. The analytical technique used in this research is the Statistical Package for the Social Sciences (SPSS). The results of this study indicate that personal factors, organizational factors, non-organizational factors, and self-efficacy have a positive and significant effect on organizational commitment. Based on the test results, the coefficient of determination R2 adjusted is 96,2%. Keywords: Personal Factors, Organizational Factors, Non-Organizational Factors and Self Efficacy, Organizational Commitment.